2006
DOI: 10.1038/nbt1253
|View full text |Cite
|
Sign up to set email alerts
|

Deviant effects in molecular reaction pathways

Abstract: In biological networks, any manifestations of behaviors substantially 'deviant' from the predictions of continuousdeterministic classical chemical kinetics (CCK) are typically ascribed to systems with complex dynamics and/or a small number of molecules. Here we show that in certain cases such restrictions are not obligatory for CCK to be largely incorrect. By systematically identifying properties that may cause significant divergences between CCK and the more accurate discrete-stochastic chemical master equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 49 publications
5
122
1
Order By: Relevance
“…This is the presented discreteness-induced inversion effect. Although a few recent papers [34][35][36][37]23,30 have studied the renormalization of the probability distribution or of the steady-state concentrations with volume, to our knowledge, this is the first time that a discreteness-induced inversion effect has been found and studied in detail.…”
Section: Discussionmentioning
confidence: 94%
“…This is the presented discreteness-induced inversion effect. Although a few recent papers [34][35][36][37]23,30 have studied the renormalization of the probability distribution or of the steady-state concentrations with volume, to our knowledge, this is the first time that a discreteness-induced inversion effect has been found and studied in detail.…”
Section: Discussionmentioning
confidence: 94%
“…In practice, 2 0 β = implies that opposing quadratic reactions of the type are excluded. Note that (2) and (4) are redundant in the sense that they are both implied by (3). However, as we saw in Section 3.3, in (4) it is often possible to find sharper constants M and µ by considering this bound in isolation.…”
Section: Assumption 49 For Argumentsmentioning
confidence: 91%
“…Such models are often thought to be more accurate than conventional rate-diffusion laws, yet remain more manageable than, say, descriptions formed at the level of individual molecules. Indeed, several studies [1]- [3] have showed that noisy models have the ability to capture relevant phenomena and to explain actual, observed dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The droplet cartoon represents the result of a degradation reaction. All the reactions in this model are always assumed to be elementary, see for instance (Samoilov and Arkin, 2006). However, let us just consider reaction (r2), which is a gene transcription reaction whereby a molecule of mRNA is produced.…”
Section: Do We Need To Worry About?mentioning
confidence: 99%